2022
DOI: 10.3390/gels8070412
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chitosan-Decorated Nanoemulsion Gel of 5-Fluorouracil for Topical Delivery

Abstract: (1) Background: The present study aimed to prepare chitosan-coated nanoemulsion gel containing 5-fluorouracil for enhanced topical delivery. (2) Methods: To formulate the nanoemulsion gel, oleic acid was used as the oil phase and Carbopol 940 as a gelling agent. Chitosan was used as a coating agent to control the release of 5-FU. Drug–excipient compatibility was evaluated using ATR-FTIR. The prepared nanoemulsion formulations were characterized based on particle size distribution, zeta potential, % encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…On the other hand, it is sensitive to pH, which is not suitable for oral. According to the literature [ 13 , 21 ], GO/HPC/CS@5-Fu aerogel is suitable for skin implants or intratumoral injection. Future work will focus on skin drug retention and tumor growth inhibition testing after drug administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is sensitive to pH, which is not suitable for oral. According to the literature [ 13 , 21 ], GO/HPC/CS@5-Fu aerogel is suitable for skin implants or intratumoral injection. Future work will focus on skin drug retention and tumor growth inhibition testing after drug administration.…”
Section: Resultsmentioning
confidence: 99%
“…Among the natural polysaccharides, chitosan (CS) has attracted much attention in medical fields [ 11 , 12 ] and is widely used for the loading and release of 5-Fu. CS-decorated nanoemulsion gel used for the topical delivery of 5-Fu was reported by the group of Lim [ 13 ]. The incorporation of a nanoemulsion into CS gel extended the half-life and enhanced the skin’s drug retention, which is suitable for the treatment of melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…The ATR-FTIR spectra of drug 5FU, alginate, chitosan, nanoparticles, and hydrogels are shown in Figure 2 . We found that 5FU has the characteristic peaks at 2992 (N–H stretching vibrations), 2883 (C=H stretching vibrations), 1723 (C=O group of ketone), 1505 and 1253 cm −1 (stretching vibration of C=N and C=F, respectively) [ 38 ]. The characteristic FTIR peaks of chitosan were at 3390, 2977, 1665, and 1401 cm −1 , and for alginate were at 3121, 2928, 1404, and 1050 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the medium was maintained at 32 and 37 °C. At specific time intervals (0, 0.5, 1, 2, 4, 8, 12, 16, 20, and 24 h), 2 mL of sample was collected and analyzed on UV spectroscopy at 265 nm [ 38 ]. The in vitro release data obtained, were fitted into Korsmeyer-Peppas equation (Equation (3)) for investigation of drug release mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…It is the thermostability that differentiates nanoemulsions from conventional emulsions, which have good kinetic stability but eventually phase separate with time. Thermodynamic stability studies ensure the stability of the optimized formulation [ 60 , 61 , 62 ]. The metastable formation can be detected by these tests.…”
Section: Resultsmentioning
confidence: 99%